MODERN CONCEPTUAL APPROACHES TO THE CATEGORY OF «AGROSPHERE» (Economic journal of Lesya Ukrainka Volyn National University, 2024)
An analysis of contemporary scientific approaches to defining the category of «agrosphere» has been conducted. The features of its content, components, and main aspects of sustainable development have been examined. The importance of the agrosphere for ensuring food security, economic growth, social well-being, and environmental preservation has been substantiated.Based on the aforementioned approaches, an author's definition of the researched category has been formulated, according to which the agrosphere is a complex system that integrates land use and agro-production, their economic, social, and environmental aspects, functioning based on sustainable land management, aimed at ensuring food security, sustainable development, and societal well-being. The agrosphere should include: all elements of agricultural production; the economic component; the social component; the environmental direction; and the institutional aspect. It is important to understand that the agrosphere is not static but continuously evolves under the influence of various factors.For the sustainable development of the agrosphere, it is necessary to implement innovative technologies and practices, invest in infrastructure and human capital, create favorable conditions for the development of the agro-industrial complex, and ensure compliance with environmental norms and standards. Only through the combined efforts of the state, business, and the public can a stable and promising agrosphere be created. Being a life-supporting system, it ideally corresponds to the principles of the sustainable development concept. And it is precisely on the foundations of sustainability that its progress should occur.
Keywords: agrosphere, conceptual approach, agro-industrial complex, sustainable development, land management.